Chronic Stress and Moral Decision-Making: An Exploration With the CNI Model - Zhang, Lisong; Kong, Ming; Li, Zhongquan; Zhao, Xia; Gao, Liuping (Frontiers in Psychology, 2018)
Stress is prevalent in our daily life, and people often make moral decision-making in a stressful state. Several studies indicated the influence of acute stress on moral decision-making and behavior. The present study extended the investigation to chronic stress, and employed a new approach, the CNI model, to add new insights regarding the mechanism underlying the association between chronic stress and moral decision-making. A total of 197 undergraduates completed the Perceived Stress Scale and made moral decision-making on a series of deliberately designed moral dilemmas. The results indicated that higher chronic stress was related to more deontological moral choices. The process-dissociation analyses revealed that chronic stress was marginally significantly associated with deontological inclinations but not with utilitarian inclinations. And the CNI model analyses suggested that the high-stress group (above the median) showed a stronger general preference for inaction than the low-stress group (below the median) did, but there were no significant differences in sensitivity to consequences or sensitivity to moral norms between the two groups. Finally, the implications of the findings were discussed.